SUPERMAKET DIVIDEND DISTRIBUTION POLICY - Yusuf Wibisono; M. Sholihun; Nani Hanifah (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
This study aims to examine the development of the management of Lumajang Supermarkets Amanah Supermarkets, which was established in 2012 with its own capital and sell shares to the public as long as approximately seven can run well in the midst of business competition and can earn profits or profits stably, so as to divide dividends to shareholders. This research is a qualitative descriptive study. The data was obtained from the Lumajang Shirkah Amanah Self-Service report for the past three years. From the profits obtained, the management makes a policy of profit sharing through the General Meeting of Share Shares (GMS). The provisions include net profit before being distributed to shareholders, issued in advance by 25% for business development, 2.5% for managers, 2, 5% for organizations, 2.5% for infaq/ zakat syirkah, and 1% for shareholder shopping rewards. Dividend distribution policy is influenced by several factors, including corporate liquidity, profitability and is supported by earnings stability.